HPTLC ANALYSIS AND IN VITRO ANTIHEMOLYTIC ACTIVITY OF FLAVONOIDS FROM CROTALARIA GLOBOSA - V.DEEPHA,; R.PRAVEENA,; K.SADASIVAM, (International Journal of Pharma and Bio Sciences, 2014)
Antioxidants generally possess the ability to protect the body from damage caused by free radical induced oxidative stress and disorders. Polyphenolics, especially flavonoids from plants serve as a good source of antioxidants. Investigation on the efficiency of these phenolics is of interest during recent years. The purpose of this work is to determine the total phenolic content, total flavonoid content and total tannin content of ethyl acetate and ethanol fractions from a novel plant source; Crotalaria globosa. In vitro investigation of antihemolytic activity for the bioactive ethyl acetate fraction (IC50 = 184.06 ± 1.94) revealed C.globosa leaves to be a good antioxidant. Further, high pressure thin layer chromatographic analysis is also carried out for the extracts of varying polarity of solvents which shows the presence of 14 different flavonoids. Ethyl acetate fraction yields more number of flavonoids compared to other solvent fractions. Bioactive compounds in these leaves can be suitably isolated and identified to develop new drugs which may be used to treat many ailments.